Comparison of ICU Outcomes between Intravenous Immunoglobulin and Plasma Exchange in Treatment of Mechanically Ventilated Patients with GuillainBarré Syndrome in a Neuro-Intensive Care Unit in a Govt. Hospital of Bangladesh: A Observational Cohort Study - Mallick, Uzzwal Kumar; Chowdhury, Mohammad Shah Jahirul Hoque; Hussain, Mohammad Enayet; Asaduzzaman, Mohammad; Islam, Md Sirajul; Hoque, Md Shamsul; Azam, Silfat; Islam, Md Zakirul; Mamtaz, Farhana; Kabir, Md Masud; Haque, Kazi Ikramul; Chowdhury, Md Tauhidul Islam; et al. (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: The management of Guillain-Barré Syndrome is very crucial for the outcome of the patient. Objective: The aim of the study was to compare efficacy of IvIg(Intravenous Immunoglobulin) versus PE(Plasmaexchange) in treatment of mechanically ventilation adults with GBS in neuro-intensive care unit of Bangladesh. Methodology: Thiswas a prospective, observationalcohort study, in a Neuro-ICU from 2017 to 2018. We included all patients with GBS who required mechanical ventilation (MV). We defined two groups: group 1 (group treated by IvIg: 0.4 g/kg/day for 5 days) and group 2 (group treated by PE: 5 PE during 10days, every alternate day). We collectedclinical and therapeutic aspects and outcome. Results: A total number of 49 patients (34 in group 1 and 15 in group 2) were enrolled. The mean age was 37.4±9.2 years, with a male predominance (65.3%). on electrophysiological findings, in 4(32.7%) patients had acute inflammatory demyelinating polyradiculoneuropathy (AIDP) and acute motor axonal neuropathy (AMAN) in 26 (53.1%) patients and acute motor-sensory axonal neuropathy (AMSAN) was 3(6.1%)and NCS was not done in 4(8.2%) cases. The mean length of ICU stay was 20±19.10 days and 46.60±30.02 days in IVIG and PE group respectively. The ICU stay was significantly shorter (p = 0.001) in the IvIg group than PE group. Patients receiving IvIg were early weaned of MV (p = 0.002) compared to those receiving PE with a statistical significance. Also, duration of M/V (P=.002), Need of tracheostomy (p=.005) and over all surval rate (p=.007) was significantly in favoue of IvIg group than PE group. Out of 49 patients, total 3 patients were died and they all were AMAN variety. Conclusion: Our work reveals a meaningful difference for the MV duration, ICU stay, weaning and excellent recovery in IvIg group compared to PE group in terms of less complcations. Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 118-122